A new time delay calibration method to improve the service performance of RDSS in the BDS. Issue 10 (15th November 2020) - Li, Xiaojie; Hu, Xiaogong; Guo, Rui; Tang, Chengpan; Liu, Shuai; Huang, Shuanglin; Jie, Xin; Pu, Junyu; Chen, Jianbing
Abstract: The radio determination satellite service (RDSS) is an advantageous and unique aspect of the BeiDou Navigation Satellite System (BDS) because other satellite navigation systems do not incorporate the RDSS. Due to the ageing of RDSS equipment, there is a long-term drift in various types of RDSS equipment time delays. There are some differences in the RDSS positioning accuracy with the change in the out-station beams, which seriously affects the positioning accuracy and service capability of the RDSS system. At present, the time delay calibration method involves sending the device to the equipment verification field to remeasure the time delay, which is cumbersome and time-consuming. The service performance and availability of the RDSS system have become greatly degraded. Therefore, a simple and efficient RDSS time delay calibration method has become an important topic for the global BeiDou system. In this study, the time delays of all channels, in-station beams, and out-station beams were obtained by the O-C method (O is the measured value and C is the theoretical value). The experiments were performed using BeiDou RDSS data in continuous 8-day tests involving five RDSS users. The results showed that the time delay accuracies of the RDSS channels, in-station beams, and out-station beams were 2.37 ns, 1.63 ns, and 2.39 ns, respectively. The positioning tests were performed based on the original and adjusted delays. The mean horizontal positioning accuracy of the five RDSS users improved from 19.71 to 4.14 m, with an average increase of 77%. The positioning accuracy achieved in this paper is much better than that of 20 m in the Beijing calibration area at present.